2012
DOI: 10.1136/jclinpath-2012-200746
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutational status of endoscopic biopsies matches resection specimens

Abstract: This study shows perfect correlation between KRAS mutation status in biopsy and resection specimens from an individual patient, and suggests that biopsy material is adequate for KRAS mutational analysis in CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Endoscopic samples may be useful in rectal adenocarcinoma specimens with low tumour cellularity, after neoadjuvant treatment. The reliability of endoscopic biopsy has also been proved by two very recent studies showing that the KRAS mutant rate is highly concordant in matched endoscopic and resection specimens 20 21. However, in our series in 8.0% of biopsies the residual material following standard histology and ancillary techniques was insufficient.…”
Section: Discussionsupporting
confidence: 56%
“…Endoscopic samples may be useful in rectal adenocarcinoma specimens with low tumour cellularity, after neoadjuvant treatment. The reliability of endoscopic biopsy has also been proved by two very recent studies showing that the KRAS mutant rate is highly concordant in matched endoscopic and resection specimens 20 21. However, in our series in 8.0% of biopsies the residual material following standard histology and ancillary techniques was insufficient.…”
Section: Discussionsupporting
confidence: 56%
“…The same KRAS point mutation was identified in the biopsy and in the corresponding resection specimens in 12/12 cases 37. In a larger series (n=125) of paired samples, concordance of KRAS mutational status between biopsy and resection specimens was very high regardless of the method used 38.…”
Section: The Samplementioning
confidence: 76%
“…Eight (11%) studies included details on the size of the biopsies . However, biopsy size reporting varied from being descriptive ‘usually measuring approximately 2–3 mm’ or ‘approximately 2 mm in size’ to measurements of areas; mean area (1 mm 2 ), median and range area (1.92 mm 2 , 0.99–3.37 mm 2 ), diameters (1–5 mm and minimum diameter of 2 mm in greatest dimension), length (mean length (1 mm)) and weight (weight range: 5–80 mg) . Only one study described how the reported measurements were obtained …”
Section: Resultsmentioning
confidence: 99%